Pendidikan multikultural: konsep, urgensi, dan implementasi dalam dunia pendidikan - Selvia, Gita (Maliki Interdisciplinary Journal, 2025)
Multicultural education is an educational approach that emphasizes the importance of recognizing, appreciating, and integrating cultural diversity within the learning process. In the context of Indonesia’s plural society, multicultural education is highly relevant to shaping students’ character to be tolerant, democratic, and capable of living harmoniously amidst diversity. This article aims to explain the concept of multicultural education, its urgency, and its implementation strategies in the Indonesian educational system. Through literature review, the study finds that multicultural education can be integrated through curriculum design, participatory teaching methods, inclusive school environments, and teacher competency development. However, its implementation still faces challenges, such as limited teacher understanding and the persistence of exclusivist attitudes in society. Therefore, synergy among the government, educational institutions, and communities is essential to realize multicultural education effectively.